What is the best treatment for plantar warts?. Issue 6 (June 2018) - Winterton, Seth; Daly, Sarah
Abstract : EVIDENCE‐BASED ANSWER : Topical salicylic or lactic acid leads to slightly higher clinical cure rates (66% vs 50%) compared with placebo/no treatment for the treatment of plantar warts (SOR: A, meta‐analysis of RCTs) and is recommended first‐line treatment (SOR: C, expert opinion). Cryotherapy and placebo both have a 25% cure rate (SOR: B, RCT), yet cryotherapy is also recommended as first‐line treatment of plantar warts (SOR: C, expert opinion). Combining salicylic acid and cryotherapy does not improve cure rates (SOR: A, meta‐analysis of RCTs). Alternative interventions include laser, topical 5‐fluorouracil, topical immunotherapy, hyperthermia, dithranol, formaldehyde, glutaraldehyde, photodynamic therapy, and podophyllotoxin (SOR: C, expert opinion).